Two new species of the subgenus Tipula (Emodotipula) Alexander, 1966 (Diptera, Tipulidae) from southwest China - Yang, Qi-Cheng; Mo, Li-Ling; Wang, Jing; Liu, Xiao-Yan; Yang, Ding (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •Two new species are described and illustrated from China.•Added two known species to the Fauna of China.•A key to the species of Emodotipula from China is presented. Only four species of the subgenus Emodotipula Alexander, 1966 were known to occur in China. Two new species, Tipula (Emodotipula) chayuensis, sp. nov., and Tipula (Emodotipula) kangdingensis, sp. nov., are described and illustrated. A key to the species of Tipula (Emodotipula) from China is presented. LSID: urn:lsid:zoobank.org:pub:C96BF4D7-68CD-4F5F-9EAA-FF2909A419FF.